PROFESSOR E.M. LAZKO – AN OUTSTANDING SCIENTIST AND PATRIARCH OF LVIV SCHOOL OF GEOLOGY AND PRECAMBRIAN METALLOGENY: TO THE 100TH ANNIVERSARY - Shatalov, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Main, determinative for that time ideas and results of Prof. E.M. Lazko’s investigations are presented. Among the main topics discussed, that form the basis and determined peculiarities of scientific school on Precambrian geology and geological-and-formation investigation developed by him at Lviv University, him about are such as specifity of early stages of the Earth’s crust evolution and its irreversible development, application of paragenetic method for geologic formation investigations of Precambrian complexes and wide implementation of this method into geological practice, particularly during geological survey works on the Ukrainian shield. Main directions of the metalogenic investigations of the Early Precambrian that carried out by E.M. Lazko and their relations with geological formation researches of the shields are considered. The contribution of representatives of E.M. Lazko’s scientific school in the development of formational geology, stratigraphy, magmatic geology and tectonics of Ukranian shield is considered. These investigations landmarked the creation of of integrated geological model of the early Earth’s evolution.